The Eigenvalue Perturbation Bound for Arbitrary Matrices (Journal of Computational Mathematics, 2006)
In this paper we present some new absolute and relative perturbation bounds for the eigenvalue for arbitrary matrices, which improves some recent results. The eigenvalue inclusion region is also discussed.
Keywords: Eigenvalue perturbation bound; Jordan canonical form; Frobenius norm; Spectral norm; Inclusion region.